The Recipe Club : - Israel, Andrea (Polhemus Press, 2009)
Includes recipes: All-day bread and breakfast (Better-late-than-never zucchini quickbread -- Catcher in the rye bread -- Count-on-it cornbread -- Currant and ginger scones -- Dorm room oatmeal with dried fruit & nuts -- Earth Day yogurt -- Luck o' the Irish soda bread -- Mighty math muffins -- Worry-free waffles) -- Cheese (Double date blintzes -- Welsh "rabbit")...